Vehicle detection system using tunnel magnetoresistance sensor - Nurul A’in, Nadzri; Chai, Kar Hoe; Mohd Mawardi, Saari; Saifuddin, Razali; Mohd Razali, Daud; Hamzah, Ahmad (Springer, 2018)
Vehicle detectors are useful to provide essential information such as parking occupancy and traffic flow. To create one robust vehicle detector which works not only in controlled environment (i.e. indoor), but it should also work in outdoor environment, a vehicle detection using magnetic approach is proposed. The magnetic signal of a vehicle will be measured based on magnetic remanence technique where it will be processed to a cloud database. To achieve a low-cost and sensitive system, a Tunnel Magnetoresistance (TMR) sensor is employed. With the combinations of software filter and state machine’s algorithm, the occupancy of the car park can be identified with high accuracy. After a few series of real field testing, it is shown that a vehicle in a parking lot can be detected by measuring the surrounding magnetic field that is disrupted by the presence of vehicles. The proposed system is tested for forward and reverse parking, and it shows a high accuracy detection for a B-segment sedan car. It can be expected that by using the proposed technique, detection of vehicles using a low-cost system with capability of online monitoring can be realized.